THE IMPACT OF THE STRATEGIC VISION STATEMENT ON PROMOTING SUSTAINABLE DEVELOPMENT PRACTICES IN IRAQI UNIVERSITIES / A FIELD STUDY IN A NUMBER OF PUBLIC AND PRIVATE UNIVERSITIES IN BAGHDAD - Zahraa Saad Sabri; Zainab Mohammed Abd; Sabah Mohammed Obaid (Scholar Express Journals, 2025)
The research aims to test and know the impact of the strategic vision in achieving and supporting sustainable development practices in a number of public and private universities in Baghdad, by finding a solution to the basic problem that was formulated with the following question (Does the strategic vision affect the achievement and support of sustainable development practices?). The research has great importance in drawing attention to the importance of stating the strategic vision and its nature and knowing its impact in achieving and supporting the application of sustainable development practices. It is necessary to work on establishing an organizational culture among the research sample regarding the importance of stating the strategic vision in achieving many advantages and directing efforts towards the best and most profitable practices. Thus, the main hypothesis of the research was formulated, which aims to find both the correlation and influence of the research variables, namely (there is a significant statistical effect of the strategic vision on sustainable development). To test these hypotheses, field research was adopted, which was applied in a number of public and private universities in Baghdad. Data was collected based on a questionnaire form, and the research sample amounted to 70 individuals from department heads and their assistants, professors and employees in the universities of the research sample. Statistical methods were adopted, which are: Using the programs ( EXCEL 2010 ), ( SPSS V 26 ) , and (SMARTPLS 4), this data was analyzed in order to calculate the coefficient of variation, standard deviation, and correlation coefficient, and to test the research hypothesis. The research results showed the existence of a significant correlation between the strategic vision and sustainable development, and the existence of a significant impact of the strategic vision on sustainable development .
Keywords: Strategic Vision; Sustainable Development